2014
DOI: 10.1097/ccm.0b013e3182a63fbf
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Perfusion as a Target for Fluid Resuscitation in Experimental Circulatory Shock*

Abstract: This study demonstrates that the relationship between the systemic and regional perfusion is dependent on the underlying cause of circulatory shock. Further research will have to demonstrate whether different microvascular perfusion variables can be used as additional resuscitation endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 46 publications
1
32
0
2
Order By: Relevance
“…In an observational study, Hernandez and colleagues reported that early recovery of peripheral perfusion indices (such CRT, T c-toe , and P (v-a) CO 2 ) is a marker of successful resuscitation of septic shock patients. In an animal study, Van Genderen et al [70] reported a relationship between central and peripheral markers of perfusion during resuscitation of experimental shock; however, the rate of normalization of perfusion markers was dependent on the underlying type of shock. A randomized controlled trial (RCT) investigated the perfusion-based approach during resuscitation of 30 septic shock patients was conducted by the same group of authors [71].…”
Section: Perfusion-guided Resuscitationmentioning
confidence: 99%
“…In an observational study, Hernandez and colleagues reported that early recovery of peripheral perfusion indices (such CRT, T c-toe , and P (v-a) CO 2 ) is a marker of successful resuscitation of septic shock patients. In an animal study, Van Genderen et al [70] reported a relationship between central and peripheral markers of perfusion during resuscitation of experimental shock; however, the rate of normalization of perfusion markers was dependent on the underlying type of shock. A randomized controlled trial (RCT) investigated the perfusion-based approach during resuscitation of 30 septic shock patients was conducted by the same group of authors [71].…”
Section: Perfusion-guided Resuscitationmentioning
confidence: 99%
“…(30-33) In cardiogenic shock, for example, all microcirculatory variables undergo change, such as reductions in the diameter of arterioles and the functional capillary density. (30-33) In patients with heart failure, intravenous infusion of nitroglycerin has been able to increase functional capillary density, even with a reduction in cardiac filling pressures, demonstrating the independence of the microcirculation in relation to macro-hemodynamic variables and their dynamic character. (31,32) …”
Section: Microcirculationmentioning
confidence: 99%
“…Coherence between the systemic circulation and the MC is lost when improvements in systemic parameters are not reflected by improvements in the MC [1]. This issue may occur particularly in states of shock, inflammation, reperfusion, and infection, as well as resuscitation damage to normal cellular sensing mechanisms [1, 5154, 88]. In adults, the loss of coherence predominately occurs in sepsis [52, 53, 56].…”
Section: Introductionmentioning
confidence: 99%